If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -5) = 3(3x + 2) Reorder the terms: 4(-5 + 2x) = 3(3x + 2) (-5 * 4 + 2x * 4) = 3(3x + 2) (-20 + 8x) = 3(3x + 2) Reorder the terms: -20 + 8x = 3(2 + 3x) -20 + 8x = (2 * 3 + 3x * 3) -20 + 8x = (6 + 9x) Solving -20 + 8x = 6 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -20 + 8x + -9x = 6 + 9x + -9x Combine like terms: 8x + -9x = -1x -20 + -1x = 6 + 9x + -9x Combine like terms: 9x + -9x = 0 -20 + -1x = 6 + 0 -20 + -1x = 6 Add '20' to each side of the equation. -20 + 20 + -1x = 6 + 20 Combine like terms: -20 + 20 = 0 0 + -1x = 6 + 20 -1x = 6 + 20 Combine like terms: 6 + 20 = 26 -1x = 26 Divide each side by '-1'. x = -26 Simplifying x = -26
| http://media.apexlearning.com/Images/200907/09/a2944e49-cb84-417a-9f9f-32fb31b69710.gif | | 2x(1)-y=5 | | 16-5r=-3(2r-8) | | 6X+8=-4x-2 | | -b^2-10b+36=0 | | 2x(0)-y=5 | | 5y+17=3x+7 | | 3.5-6x=x-1.75 | | 3.5-6=x-1.75 | | 44.5=-35.6+m | | x-8+x+7+90=180 | | 9x-15=49 | | 3.56x=x-1.75 | | (x/5)-1 | | -10=-10+v | | -7v-4-6=33 | | 5*(x+1)=3*(x-7) | | y-28=50 | | 0.8+d=-0.7 | | 1*(1+x^3)=1.5 | | x^2m-x^2-2x+2m-3=0 | | 3x-20+90+x=180 | | x^2+3x-6=-6 | | 16=2(3c-9) | | 2y+3=8.6 | | 15+a=-10 | | 8-2x=9x+2 | | -16=x+16 | | -5(-6w+5)-9w=7(w-4)-9 | | 0,5-3x=x+1.1 | | 16a-6.5=9.5 | | 2x+3x-15=12+8 |